Allergic contact dermatitis to chlorhexidine‐containing antiseptics and their excipients in children: A series of six cases. Issue 1 (13th December 2022) - Kefala, Kalomoira; Ponvert, Claude
Abstract: Contact allergy to skin disinfectants is not often recognized in children. We report the cases of six children (1–16.5 years old) with allergic contact dermatitis to ingredients commonly contained in commercial antiseptic and cosmetic products. Patch test responses to chlorhexidine, benzyl alcohol, and benzalkonium chloride varied from one child to another one, but most children were sensitized to at least two components. In several of the cases, exposure had initially occurred in the neonatal period, but diagnosis occurred only after multiple reactions of increasing severity.